Reconfigurable antenna design for soil testing to improve soil quality - Dinesh Kumar, R; P. Ramesh, G (International Journal of Engineering and Technology, 2018)
The Multi-band Reconfigurable antenna used to achieve the different frequency with low return loss. It achieves the variety applications like soil testing using the antenna data transmission and makes the quality of the soil to improve the production. Effectiveness of the work used to propose that the antenna designed to sense the chemical content of the soil and report the data with the frequency of 2.4 GHz to the operator, which makes the operator to have good crop at the right time. This antenna design also used to have the different frequency of data transmission in the single structure, it produces the frequencies likeWLAN at 1.5GHz, GPS at 2.4GHz, WiMAX at 3.27 GHz and Wi-Fi at 5.17 GHz, which designed using the T-shaped stub and two E-shaped stubs. The Existing antenna can transmit only three frequencies with 70% output efficiency but the proposed antenna design can transmit four different frequencies with 80.5% output efficiency. The simulated and the measured results of four investigated bands are lies between -12.3 dB and -15.5 dB with the Bandwidth of 10KHz which show that the antenna has better performance in all frequency bands. It offers the radiation Patten, return loss, peak gain and efficiency at low cost with high accuracy using microstrip patch antenna.Â Â